COVID-19 and social determinants of health : wicked issues and relationalism - Bonner, Adrian (Bristol University Press, 2023)
Health and socio-economic consequences of the COVID-19 pandemic have been exacerbated by central government-imposed austerity budgeting by local authorities and the health service. This book, part of the Social Determinants of Health series, extends the ideas developed in the previous volumes by reviewing the impact of COVID-19 on local and national governance from the perspectives of public health, social care and economic development. Drawing on case studies from across the UK and beyond, it explores the pandemic and other 'wicked' issues including climate change, homelessness, unemployment and domestic abuse through the lens of relationalism, and proposes necessary system changes.